2012
DOI: 10.1002/ase.1277
|View full text |Cite
|
Sign up to set email alerts
|

The translucent cadaver: An evaluation of the use of full body digital x‐ray images and drawings in surface anatomy education

Abstract: It has been noted by staff at the Faculty of Health Sciences, Stellenbosch University that medical students neglect the study of surface anatomy during dissection. This study reports on the novel use of Lodox(®) Statscan(®) images in anatomical education, particularly the teaching of surface anatomy. Full body digital X-ray images (Lodox Statscan) of each cadaver (n = 40) were provided to second year medical students. During dissection students were asked to visualize landmarks, organs, and structures on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…Moreover, the use of bony landmarks may be limited in areas with deeper bone structures, for example, in the pelvic region. 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the use of bony landmarks may be limited in areas with deeper bone structures, for example, in the pelvic region. 1 …”
Section: Discussionmentioning
confidence: 99%
“…The physiological changes in blood flow during acupuncture needle insertion have been explored using different forms of Doppler imaging including laser Doppler perfusion imaging, 1 laser Doppler flowmetry, 2 and ultrasound colour Doppler. 3 However, a review of the literature found no study exploring the effects of acupuncture on blood vessel size and muscle strain.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Western medical education has utilised X-rays 1 and CT 2 of cadavers to enable students to better comprehend human anatomy, with positive responses. In a previous study, we explored the potential use of ultrasonography for the location of anatomical points.…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate knowledge of anatomy, particularly of surface anatomy, is needed to undertake physical examinations and interventional procedures safely and effectively and to interpret diagnostic images. For many general practitioners, the vast majority of the anatomy that they use may be surface anatomy (Kotzé et al, 2012). For interventionists, direct visualization techniques, e.g., ultrasound guidance in regional anesthesia, have not displaced the need to know the relevant anatomy, including surface anatomy: for anesthetists and anesthesiologists, the mantra that ''regional anesthesia is applied anatomy.…”
mentioning
confidence: 99%
“…Assuming that surface anatomy, hopefully evidence-based, is not consigned to the long grass, when and how it should be taught? Novel pedagogic approaches, such as using body painting or drawing on a ''translucent cadaver'' (laminated photographs of full body digital X-rays), appear to engage students in the process of knowledge acquisition (Op Den Akker et al, 2002;Aggarwal et al, 2006;McMenamin, 2008;Finn and McLachlan, 2010;Finn et al, 2011), but do not necessarily aid the subsequent implementation of that knowledge in the clinic (Kotzé et al, 2012). This resonates with my experience that the surface anatomical knowledge of some recent medical graduates and surgical trainees often bears a striking resemblance to the childhood guessing game of ''pin the tail on the donkey.''…”
mentioning
confidence: 99%